2012
DOI: 10.1371/journal.pone.0044877
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Structural MRI Images in Alzheimer's Disease from the Perspective of Ill-Posed Problems

Abstract: BackgroundMachine learning neuroimaging researchers have often relied on regularization techniques when classifying MRI images. Although these were originally introduced to deal with “ill-posed” problems it is rare to find studies that evaluate the ill-posedness of MRI image classification problems. In addition, to avoid the effects of the “curse of dimensionality” very often dimension reduction is applied to the data.MethodologyBaseline structural MRI data from cognitively normal and Alzheimer's disease (AD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…The feature selection uses the regularized logistic regression framework (Friedman et al, 2010) that produces a path of feature subsets with different cardinalities (called regularization path ), and has been used widely in previous works (Huttunen et al, 2012, 2013; Ryali et al, 2010) for the multi-voxel pattern analyses of functional neuroimaging data as well as for AD related studies using structural MRI data (Ye et al, 2012; Casanova et al, 2011a,b, 2012; Shen et al, 2011; Janoušová et al, 2012). As the RLR procedure is a supervised learning method, the input has to be fully labeled data.…”
Section: Methodsmentioning
confidence: 99%
“…The feature selection uses the regularized logistic regression framework (Friedman et al, 2010) that produces a path of feature subsets with different cardinalities (called regularization path ), and has been used widely in previous works (Huttunen et al, 2012, 2013; Ryali et al, 2010) for the multi-voxel pattern analyses of functional neuroimaging data as well as for AD related studies using structural MRI data (Ye et al, 2012; Casanova et al, 2011a,b, 2012; Shen et al, 2011; Janoušová et al, 2012). As the RLR procedure is a supervised learning method, the input has to be fully labeled data.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach that operates directly in the voxel space was proposed by Casanova et al [241] who used penalized logistic regression and coordinate-wise descent optimization to overcome these problems of large scale classification. A subsequent paper by the same group [395] examined classification methods from structural MRI from the perspective of linear ill-posed problems and in the absence of dimensionality reduction techniques. They found that logistic regression, linear regression, and SVM classifiers were robust to increased dimensionality.…”
Section: Methods Papersmentioning
confidence: 99%
“…Casanova et al (2012) used linear SVM, regularized logistic regression, and linear regression classifier (LRC) for the classification of patients with AD. Rangini and Jiji (2013) used SVM and AdaSVM for hippocampal segmentation.…”
Section: Support Vector Machinementioning
confidence: 99%
“…Casanova et al (2012) used LRC to classify the structural MRI images in AD and compared the performance of LRC and SVM based on different dimensions and sample sizes. In that work, the classification feature vectors were created as GM voxels obtained by segmentation.…”
Section: Logistic Regression Classificationmentioning
confidence: 99%